Imported tick-borne encephalitis in a traveller returning to North Macedonia from Switzerland June 2024 - Jakimovski, Dejan; Poposki, Kostadin; Bosilkovski, Mile; Bogdan, Ivana; Simin, Verica; Banovic, Pavle (Oxford University Press (OUP), 2025)
A 26-year-old man from North Macedonia developed tick-borne encephalitis (TBE) after a tick bite in Switzerland, experiencing severe neurological symptoms before a full recovery. This case highlights the importance of vaccination and awareness for travellers from non-endemic regions visiting TBE-endemic areas.